Influence of cryogenic treatment on mechanical and interfacial properties of carbon nanotube fiber/bisphenol-F epoxy composite. (15th September 2017) - Shao, Yiqin; Xu, Fujun; Liu, Wei; Zhou, Mengjie; Li, Wei; Hui, David; Qiu, Yiping
Abstract: The effects of cryogenic treatment (−196 °C) on properties of the carbon nanotube (CNT) fiber/epoxy composite are investigated using a temperature controlled cooling process with low cooling rate. The CNT fiber/epoxy single fiber composite fragmentation test is performed in conjunction with electrical resistance measurements to compare the interfacial properties at ambient and cryogenic temperatures. Weibull distribution for CNT fiber strengths shows a decreased variation (the shape parameter increases from 4.98 to 6.93) for cryo-treated fibers although their mechanical properties are not significantly influenced by the treatment. The electrical resistance measurement shows an increased electrical resistance changing rate with strain for the cryogenic treated sample, indicating better fiber/matrix interaction. In addition, the cryogenic treatment also improves interfacial bonding strength by 31% owing to the effect of differential thermal shrinkage for the CNT fiber and epoxy. An asymmetrical interfacial stress distribution is observed corresponding to the asymmetrical birefringence patterns of the fragmented fiber in the single fiber composite, which could be due to the twisted structure of the CNT fiber.